2015
DOI: 10.17957/ijab/14.0024
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between DNAJA1 Expression and Beef Tenderness: Effects of Electrical Stimulation and Post-mortem Aging in two Muscles

Abstract: Previous studies have demonstrated that DNAJA1 could be a good indicator of beef toughness in Longissimus thoracis muscle from Charolais young bulls. This study aimed to check if relationship between DNAJA1 expression and beef tenderness is valid in two muscles, which differ in toughness from Angus steers with or without electric stimulation at different times of post-mortem ageing. Electric stimulation did not significantly affect DNAJA1 expression at the time of slaughter. But, RNA degradation soon after sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Improvement of tenderness by meat aging involves several proteolytic systems responsible for the degradation of muscle proteins (Sami et al, 2015). Generally, the tenderness of beef improves significantly over the aging period in a musclespecific manner (Nair et al, 2019).…”
Section: Argenis Rodasgonzálezmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement of tenderness by meat aging involves several proteolytic systems responsible for the degradation of muscle proteins (Sami et al, 2015). Generally, the tenderness of beef improves significantly over the aging period in a musclespecific manner (Nair et al, 2019).…”
Section: Argenis Rodasgonzálezmentioning
confidence: 99%
“…In the latter study, the vacuum aging treatment increased the proportion of tender loin steaks from 42.9 % (aged for 2 d) to 71.4 % (aged for 14 d). According to Sami et al (2015) to effectively tenderize longissimus muscles (i.e., by reaching a WBSF < 43.0 N) the vacuum aging period had to last at least 21 d. In fact, Vilella et al (2019) reported that 28 dvacuumaged samples resulted in lower WBSF values than those from the control group, and 87 % of the aged steaks were classified as tender (WBSF < 40.1 N).…”
Section: Effects Of Postmortem Treatmentsmentioning
confidence: 99%